2000
DOI: 10.3168/jds.s0022-0302(00)75080-6
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effect of Tannic Acid on Composition and Ruminal Degradability of Bermudagrass and Alfalfa Silages

Abstract: We measured the effects of the addition of tannic acid on chemical composition and crude protein (CP) ruminal degradability of bermudagrass, cv. coast cross (Cynodon dactylon L.) and alfalfa (Medicago sativa L.) silages with nylon bags incubated in the rumen of two fistulated lactating cows. Silage pH was greater for alfalfa than for bermudagrass. The addition of tannic acid had no effect on silage pH. Ammonia N was greater in alfalfa than in bermudagrass silage. Treated and control silages had similar ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
0
16
1
Order By: Relevance
“…Addition of 8% and 10% pistachio PB also increased (P < 0.05) CP contents of silages. This can be explained with the formation of tannin-protein complexes, which can cause a reduction in the rate of microbial degradation of proteins (Santos et al 2000), and relatively higher CP content of pistachio PBs than corn silage material. Pistachio PB increased (P < 0.05) ADF values of silages depending on the increment level in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of 8% and 10% pistachio PB also increased (P < 0.05) CP contents of silages. This can be explained with the formation of tannin-protein complexes, which can cause a reduction in the rate of microbial degradation of proteins (Santos et al 2000), and relatively higher CP content of pistachio PBs than corn silage material. Pistachio PB increased (P < 0.05) ADF values of silages depending on the increment level in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Tannins in silos, in an environment close to a neutral pH, form complex compounds with soluble protein silage, thereby preventing the degradation of proteins by microorganisms and the subsequent reduction of the ammonia nitrogen concentration. This process prevents protein losses and improves silage quality (Barry & Manley 1986;Santos et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Spraying TA on alfalfa before ensiling affected neither N concentration nor effective degradability of crude protein (CP) but reduced the percentage of CP solubilised at initiation of incubation (Santos et al, 2000). However, soya bean treatment with TA reduced ruminal degradation and intestinal digestibility of proteins (Hervas et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its availability, cost and relative purity, tannic acid has been used widely to study the effect of tannins on rumen fermentation (Driedger et al, 1969;Nishimuta et al, 1974;Murdiati et al, 1992;Zhu and Filippich, 1992;Plumlee et al, 1998;Hervas et al, 2000;Santos et al, 2000;Frutos et al, 2004;Martinez et al, 2005 and. The objective of this study was to assess the influence of spraying tannic acid (TA) on chopped alfalfa hay on in vitro rumen fermentation of dry matter (DM) and N retention by sheep fed alfalfa hay.…”
Section: Introductionmentioning
confidence: 99%
“…formaldehyde and tannic acid have been tested to improve the ensiling properties of alfalfa silage, but reports of their efficacy are inconsistent 2 . Previous studies suggested that the inoculation with lactic acid bacteria (LAB) at ensiling could improve the fermentation of legume silage by accelerating the production of lactic acid (LA) to cause occurrence of acidic conditions rapidly 3 .…”
mentioning
confidence: 99%